Fruit color and post-harvest shelf life in tomato affected by the ogc, norA, and rin alleles - Antezana Poma, Betsabé; Maluf, Wilson Roberto; Gouveia, Beatriz Tome; Oliveira, Alisson Marcel Souza de; Ferreira, Rodolfo de Paula Duarte; Carvalho, Regis de Castro (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the effects of the mutant alleles alcobaça (norA), ripening inhibitor (rin), and old gold crimson (ogc), in heterozygosity or homozygosity, on the expression of color and on the postharvest quality of fruit of experimental tomato hybrids. Fourteen hybrids with contrasting genotypic constitutions in the norA, rin, and ogc loci were evaluated in a randomized complete block design with four replicates. The following fruit postharvest quality traits were evaluated: firmness in the breaker stage, color, and soluble solids content. The rin+/rin and nor+/norA genotypes increased firmness of tomato fruit at harvest (breaker stage). The rin+/rin genotypes displayed the worst internal fruit color. There was a positive effect of ogc+/ogc in improving the internal color of rin+/rin and nor+/norA fruit, making the color similar to that of the normal genotypes. The combination of the ogc/ogc rin+/rin nor+/norA genes is effective to improve tomato fruit firmness, besides maintaining or improving internal color.